Smart grid scheduling and control based on master–slave game - Rongbo Liang; Yongjin Yu; Feiran Yang (Systems Science & Control Engineering, 2018)
Electric power dispatch is an effective management method used to ensure the safe and stable operation of the power grid, however, there will be some conflicts of interest between the power selling company and the power generation company during the dispatch process. This article aims to minimize the cost of electricity purchased by the power grid company and maximize the sales revenue of power generating company. In this paper, the decision-making space is based on the set of strategies for each power plant output and the on-grid price, proposing a master–slave game scheduling model in which the power grid company is used as the main game and power plants are the game followers. By using the cuckoo algorithm to optimize the master–slave game model, scheduling test results show that master–slave game scheduling provides better overall performance than economic dispatch.